IN SILICO BINDING INTERACTION STUDY OF MEFENAMIC ACID AND PIROXICAM ON HUMAN ALBUMIN - Djajadisastra, Joshita; Purnama, Hamka Decky; Yanuar, Arry (International Journal of Applied Pharmaceutics, 2017)
Objective: A drug can replace other drugs in the same binding position in protein plasma, increasing pharmacological response due to the increased free drug concentration. Drug shifting is critical when a compound is tightly bound to a protein. For example, a binding fraction change, from 98% to 94%, may increase the free fraction 3 times, from 2% to 6%. Knowing that there is an interaction between mefenamic acid and piroxicam on plasma protein, more specifically on human albumin, this study aimed to visualize the interaction between both drugs and human albumin in silico. Methods: This study used AutoDock4 as a molecular docking technique, obtaining binding visualizations, binding energies (Î”G), and inhibition constants (Ki) of both mefenamic acid-albumin and piroxicam-albumin bindings. Results: It is shown that the Î”G and Ki of both mefenamic acid and piroxicam are âˆ’5.47 kcal/mol (98.59 Î¼M) and âˆ’7.46 kcal/mol (3.42 Î¼M), respectively. Conclusions: The process of binding mefenamic acid to albumin can be substituted with piroxicam due to its higher Î”G and Ki values. It can be predicted that this interaction will increase the free mefenamic acid concentration in blood plasma which, in turn, enhances the therapeutic effect.